Thermal Characterization of Large Lithium-ion cells - Vishwakarma, Rajesh; Selvakumar Rajeswari, Amithesh (My University, 2025)
Accurate thermal management is critical for battery management systems (BMS) to prevent thermal runaway and optimize performance. The reliability of thermal models depends on precise characterization of material properties and heat generation, yet many existing models rely on assumed or incomplete parameters, limiting accuracy. This study investigates the thermal properties and behavior of 4695 cylindrical lithium-ion cells using a combined experimental and simulation-based approach. A custom-built isothermal calorimeter measured reversible and irreversible heat generation across various C-rates and temperatures, while entropic coefficients were determined using calorimetric and potentiometric methods to ensure consistency and validate the experimental setup. An Electrical Equivalent Circuit Model (EECM), developed with experimental and manufacturer-provided data, was integrated into a 3D electrothermal COMSOL model to analyze internal temperature distributions and heat propagation. Results show that heat generation rises significantly with increasing C-rate, with discharging producing up to 36% higher peak heat than charging, highlighting nonlinear scaling and the importance of tailored cooling strategies. Calorimeter calibration revealed systematic errors at low power, which were effectively mitigated by offset correction and noise filtering, reducing errors to below 4% at moderate to high power levels. Cooling simulations demonstrated that double-sided liquid cooling at a 60° configuration offers the best balance between thermal performance, uniformity, and practical design, outperforming single-sided and high-angle alternatives. Overall, the integrated experimental and modeling framework provides critical insights for the design of safer, more efficient thermal management systems in large-format lithium-ion batteries for electric vehicles.
Keywords: 3-D, Li-ion, Calorimeter, Potentiometer, Thermal model, Heat transfer, EECM